Powers of possibility experimental American writing since the 1960s - Houen, Alex. (Oxford : Oxford University Press, 2012)
By outlining a novel concept of literary practice 'potentialism', this text shows how opening up literary possibilities enabled writers such as Allen Ginsberg, LeRoi Jones/Amiri Baraka, William S. Burroughs, Kathy Acker, and Lyn Hejinian to tackle matters of power and politics.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Keywords: Literature, Experimental -- United States -- History and criticism; American literature -- 20th century -- History and criticism; Social problems in literature